2016
DOI: 10.1186/s12868-016-0317-0
|View full text |Cite
|
Sign up to set email alerts
|

CatWalk gait analysis in a rat model of multiple sclerosis

Abstract: Background Myelin oligodendrocyte glycoprotein (MOG)-induced experimental autoimmune encephalomyelitis (EAE) is a widely used animal model for multiple sclerosis. The characteristic feature of the MOG-EAE model in Brown Norway rats is consistent involvement of the spinal cord resulting in limb paresis. The aim of the study was to investigate whether early subclinical gait abnormalities are present in this animal model and can be detected by CatWalk XT, a fully automated gait analysis system. Furthermore, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 23 publications
0
19
1
Order By: Relevance
“…MOG33-55 peptide is an important pathogenic component contributing to EAE induction. The EAE rat model of multiple sclerosis is a representative model of multiple sclerosis because this model markedly demonstrates hind-limb paralysis, motor dysfunction and nerve damage [1,15]. MOG33-55 injection caused motor dysfunction by secreting pro-inflammatory cytokines and inflammatory exudates [7,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MOG33-55 peptide is an important pathogenic component contributing to EAE induction. The EAE rat model of multiple sclerosis is a representative model of multiple sclerosis because this model markedly demonstrates hind-limb paralysis, motor dysfunction and nerve damage [1,15]. MOG33-55 injection caused motor dysfunction by secreting pro-inflammatory cytokines and inflammatory exudates [7,21].…”
Section: Discussionmentioning
confidence: 99%
“…The rats were anesthetized by inhalation of sevoflurane (4%) in oxygen (30%) and nitrogen (70%) delivered through a face mask. As described previously [14,15], 50 μg of purified MOG 33-55 (MOG33-55) was dissolved in 200-μL saline which was homogenized (1:1 v/v) with Freund's complete adjuvant (with mycobacteria). MOG33-55 was injected intradermally through the base of the tail.…”
Section: Eae Induction and Clinical Disability Score Assessmentmentioning
confidence: 99%
“…Catwalk automated gait analyses measure changes in spontaneous gait due to joint pain. Animals pass an illuminated glass platform while gait is recorded with a video camera connected to a computer, and the changes in gait pattern, such as swing speed and stride length, are analyzed [52]. Thermal hyperalgesia is assessed using the hot plate test, where the rodent is placed on a metal surface maintained at a constant temperature.…”
Section: Behavioral Tests To Assess Pain In Oa Animal Modelsmentioning
confidence: 99%
“…Of note, the animal walks across the glass plate voluntarily which is different to the system applied in the current study. This method has been performed in the EAE model using different species such as Lewis rats [46], Brown Norway rats [47], or C57BL/6 mice [48]. In our study, we observed that MOG 35-55 immunization severely influenced the success rate of gait analysis recordings.…”
Section: Discussionmentioning
confidence: 74%